Comparison of bursting pressure on sleeve gastrectomy staple lines between stapling, buttressing, and oversewing. (February 2021) - Tolone, Salvatore; Gambardella, Claudio; del Genio, Gianmattia; Brusciano, Luigi; Ruggiero, Roberto; Lucido, Francesco Saverio; Docimo, Ludovico
Backgrounds . One of the major complications after laparoscopic sleeve gastrectomy (LSG) is represented by leaks along the staple line. Several reinforcement techniques have been proposed, but scarce data about the real strengthening offered are present. Thus, we aimed to evaluate if different reinforcements produced different bursting pressures after LSG, and then to verify if the clinical application of the stronger reinforcement produced a reduction in leakage rate. Methods. We prospectively enrolled all consecutive obese patients that underwent LSG. We tested 3 different types of staple lines, as follows: group 1, no reinforcement; group 2, bioabsorbable buttress reinforcement; group 3, invaginating overrunning barbed suture. A burst pressure test was applied to the gastric specimen by means of high-resolution manometric catheter. After burst pressure tests, a subsequent consecutive series of patients were treated with the most effective reinforcement, and rate of leaks was recorded. Results . We enrolled in total 110 obese patients; 20 patients for each group of staple line reinforcement and then other 50 consecutive patients underwent LSG with the higher burst pressure staple line reinforcement. Median burst pressures were similar in group 1 and group 2; group 3 showed a statistically significant pressure increase ( P < .0001) than group 1 and group 2, with a 5.2-fold value. Other consecutive 50 obese patients underwent LSG with overrunning reinforcement. In none of them a leak was detected. Conclusions . Reinforcement of the SG staple line, with overrunning suture, seems to drastically increase bursting pressures in an ex vivo model and it is promising when reproduced in vivo.